The Role Of Nitrite Producing Bacteria And Its Mechanism To Prevent The Dental Caries - Maghfira Izzani Maulania; Dimas Prasetianto Wicaksono; Jason Patrick Siregar; Feby Ayu Lestari; Lukas Aldhi Hannawan Siswoyo; Udijanto Tedjosasongko (Universitas Airlangga, 2021)
Background : Dental caries is the most common disease and often occurs in the oral cavity that can be found in adults nor children and until now many studies about dental caries have been established to reduce the caries level. In our daily life, nitrate (NO3-) can be found in the green vegetables which can be reduced to NO2- by some oral bacteria. NO2- can inhibit the growth and acid production of pathogenic bacteria such as Streptococcus mutans to prevent the dental caries. There have been many studies that explain the effect of NO2- as an antibacterial agent, but there are limited studies that explain about the role of NO2- on maintaining the oral health and its relation to the NO3-reduction mechanism involved the environment in the oral cavity. Purpose : To analyze the role of NO2- producing bacteria and its mechanism to prevent the dental caries. Results : The amount of NO2- in the oral cavity produced by reduction of NO3- depends on diet and the number of NO3- reducing bacteria, especially obligate and facultative anaerobes. NO2- can inhibit the growth and metabolism of cariogenic bacteria. Conclusion : NO3- reducing bacteria in the oral cavity, a diet consisting of NO3- plays an important role in the prevention of dental caries through the NO3– NO2- mechanism to reduce the number and metabolism of cariogenic bacteria.